The Financial Troubles of Said bin Taimur - Owtram, Francis (Qatar Digital Library, 2014)
The reign of Said bin Taimur was marked by financial troubles from the outset, but despite his more active role in the 1930s, a rebellion in the province of Dhofar ultimately cost him the Sultanate.
Keywords: Vie politique – Oman – 1932-1970